PENGARUH VARIASI TEMPERATUR SINTERING TERHADAP STRUKTUR KRISTAL SUPERKONDUKTOR Y0.5La0.5Ba2Cu3O7-? - Cahya Pradhana, I G.; Suharta, Wayan Gede; Widagda, I Gusti Agung (BULETIN FISIKA, 2016)
Variation of sintering temperature have been done in the synthesis  superconductors using wet-mixing method by adding  to obtain homogenous superconductors. Generally, XRD characterization and search match indicates the presence impurities of BaCO 3 , BaCuO 2 , dan CuO compounds. Variation of sintering temperature of 750 o C, 850 o C, dan 950 o C showed an increase in the volume fraction of superconductors of 57.15%, 88.78%, and 95.04%, lattice parameter a showed a decreased of 3.891178 ?, 3.886266 ?, and 3.879036 ?, b of 3.912534 ?, 3.910184 ? and 3.897226 ?. Meanwhile, lattice parameter c showed an increased of 11.600093 ?, 11.769890 ?, and 11.826884 ?,  crystal size of 73 nm, 149 nm, and 160 nm.